Pengaruh Zakat Terhadap Penurunan Kemiskinan di Kawasan Barat Selatan Aceh - Darma, Surya; Rahman, Nopijal Rizki; Amri, Khairul (Yayasan Kawanad, 2024)
Our research study aims to examine and analyze the impact of zakat distribution by Baitul Mal on reducing poverty levels in the West-South region of Aceh. Utilizing panel data from 8 regencies and cities over the period 2013-2021, the analytical model employed is panel regression with a fixed effect approach. Our study reveals that zakat distribution significantly reduces poverty levels. The larger the amount of zakat distributed, the lower the poverty level. These findings imply that regional government efforts to reduce poverty, particularly in the West-South region of Aceh, can be implemented through policy interventions related to zakat distribution. Regional governments, through Baitul Mal, must ensure that zakat recipients are indeed from the poor group.